Training Program Influence in Enhancing Employee’s Performance at F&B Service the St. Regis Bali Resort - I Putu Bayu Andreawan; Ni Nyoman Triyuni; I Ketut Astawa (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
Training is an important thing carried out by companies that provide opportunities for employees to improve their skills related to work. The study, entitled